2004
DOI: 10.1002/14651858.cd000085.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Extra-abdominal versus intra-abdominal repair of the uterine incision at caesarean section

Abstract: Ezechi 2005 {published data only} Ezechi OC, Kalu BK, Njokanma FO, Nwokoro CA, Okeke GC. Uterine incision closure at caesarean section: a randomised comparative study of intraperitoneal closure and closure a er temporary exteriorisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…There is conflicting data on the risks and benefits of exteriorizing the uterus. A Cochrane review examining six studies, which compared extra-abdominal from intra-abdominal uterine repair, found exteriorization to be associated with a significant decrease in postoperative fever [ 51 ]. Two other large studies demonstrated that there were no differences regarding intraoperative complications when comparing hysterotomy closure to either extra-abdominally or intra-abdominally [ 52 , 53 ].…”
Section: Preventionmentioning
confidence: 99%
“…There is conflicting data on the risks and benefits of exteriorizing the uterus. A Cochrane review examining six studies, which compared extra-abdominal from intra-abdominal uterine repair, found exteriorization to be associated with a significant decrease in postoperative fever [ 51 ]. Two other large studies demonstrated that there were no differences regarding intraoperative complications when comparing hysterotomy closure to either extra-abdominally or intra-abdominally [ 52 , 53 ].…”
Section: Preventionmentioning
confidence: 99%
“…1 With the objectives of applying evidence-based practices and improving maternal and neonatal outcomes, Enhanced Recovery after Surgery protocols have been adapted for Cesarean delivery, with one of the key components being the optimization of surgical technique. 2,3 An aspect that may be amenable to optimization is the method of uterine repair; uterine exteriorization may improve surgical visualization, hemostasis, and speed of repair; however, its benefits on hemostasis are controversial 4,5 and may not justify the potential added risks of nausea and vomiting, pain, and infection. [6][7][8][9] In 2015, a meta-analysis of 16 studies 10 comparing uterine exteriorization with in situ repair for Cesarean delivery reported that uterine exteriorization was associated with a non-clinically significant reduction in perioperative hemoglobin decrease, but was also associated with a delay in the return of bowel function.…”
mentioning
confidence: 99%
“…9 There was statistically no significant difference between the two groups as far as intra-operative nausea, vomiting is concerned. 5,7 Blood loss is significantly more in the non-eventrated group; uterine eventration at caesarean section is not to be condemned. 10 For active management of the 3 rd stage of labour WHO recommended uterotonics before placental delivery in all cases to prevent PPH.…”
Section: Review Of Literaturementioning
confidence: 96%
“…Exteriorization of uterus is a valid option, as demonstrated by clinical and statistical evidence. 7,8 An alternative surgical sequence of delivering the placenta in the exteriorized uterus with IMM oxytocin showing statistically significant decrease in blood loss seems to be physiologically sound procedure with significant decrease in operative time. 9 There was statistically no significant difference between the two groups as far as intra-operative nausea, vomiting is concerned.…”
Section: Review Of Literaturementioning
confidence: 99%